Lost pigs of Angola: Whole genome sequencing reveals unique regions of selection with emphasis on metabolism and feed efficiency - Sá, Pedro; Santos, Dulce; Chiaia, Hermenegildo; Leitão, Alexandre; Cordeiro, José Moras; Gama, Luís T.; Amaral, Andreia J. (Frontiers in Genetics, 2022)
Angola, in the western coast of Africa, has been through dramatic social events that have led to the near-disappearance of indigenous swine populations, and the recent introduction of European exotic breeds has also contributed to the erosion of this indigenous swine repertoire. In an effort to investigate the genetic basis of remnant indigenous pig populations in Angola (ANG) we have generated whole genomes from animals of a remote local pig population in Huambo province, which we have compared with 78 genomes of European and Asian pig breeds as well as European and Asian wild boars that are currently in public domain. Analyses of population structure showed that ANG pigs grouped within the European cluster and were clearly separated from Asian pig breeds. Pairwise FST ranged from 0.14 to 0.26, ANG pigs display lower levels of genetic differentiation towards European breeds. Finally, we have identified candidate regions for selection using a complementary approach based on various methods. All results suggest that selection towards feed efficiency and metabolism has occurred. Moreover, all analysis identified CDKAL1 gene, which is related with insulin and cholesterol metabolism, as a candidate gene overlapping signatures of selection unique to ANG pigs. This study presents the first assessment of the genetic relationship between ANG pigs and other world breeds and uncovers selection signatures that may indicate adaptation features unique to this important genetic resource.